Wildlife [videorecording (DVD)] - Dano, Paul, 1984-; Gyllenhaal, Jake, 1980-; Mulligan, Carey, 1985-; Oxenbould, Ed, 2001-; Camp, Bill; Ford, Richard, 1944- (Criterion collection, 2020)
A meticulously crafted portrait of the American nuclear family in crisis charts the rift that forms within a 1960s Montana household when the father and breadwinner abruptly departs to fight the forest fires raging nearby, leaving his restless wife and teenage son to pick up the pieces. A deeply human look at a woman's wayward journey toward self-fulfillment in the pre-women's liberation era and a sensitively observed, child's eye coming-of-age tale.